Chaotic Dynamics for Laser Diode under Unidirectional and Mutual Optical Injection with Optoelectronic Feedback - A. Hemed, Ayser; Abbas, Rasha Salah (Current Overview on Science and Technology Research Vol. 8, 2022)
Nonlinear and chaotic dynamics for a continuous emission (CW) laser diode with a Fabry-Perot cavity are being investigated experimentally to develop a new chaotic transmitter system. Uni-directional and bi-directional optical injection configurations were constructed with and without optoelectronic feedback (OEFB) and even direct modulation. Another possibility is also investigated, where the injection is reversed to observe dynamics generated in the second laser diode (LD2). Accordingly, the first laser diode (LD1) receives optical injection from LD2, which is initially mixed with self-OEFB, and then, LD2, under OEFB, receives pure optical injection from LD1. Results indicate the generation of chaotic pulsation with mode hopping in the first configuration and mode-lock at a specific bias current level in the second one. Under bi-directional optical injection, results show that the laser entered a new instability leading to a variety of more nonlinearities. One of them is the lasing mode shifting and switching. The ratio of OI was controlled by an optical attenuator and also OEFB by an RF attenuator. Mode hopping, multimode emission, mode lock, and chaotic behavior are all observed experimentally corresponding to operating conditions. The observed chaotic pulse linewidth was measured at 300 MHz, with the ability to be broader via changing detuning and injection ratio. The laser changed to emit in pulsation with a route to chaos status in which it has an FWHM of around 0.1GHz. Reversing injection led to linewidth enhancement with a very sharp FWHM, 1.5 kHz. Laser emission is perturbed due to mixed injection as if it works with OEFB, where the gain switches tend to drive the laser into pulsing states induced by that positive OEFB. For each achieved result, there exists an application, such as; chaos shifts keying, frequency mixing, and up-conversion to a new frequency to reduce the cost of high-speed electronics associated with optical communications.